Pernikahan Tanpa Izin di Lingkungan Militer: Analisis Yuridis Pertimbangan Hakim pada Kasus Pidana Militer Nomor 143 K/MIL/2016 - Ali, Nuraliah; januardy, ivans; Farina, Thea; Sibot, Yessiarie Silvany; Nugraha, Satriya (Fakultas Hukum, Universitas Palangka Raya, 2024)
Marriage without permission in the military environment is a serious violation that can disrupt discipline, operational efficiency, and the morale of soldiers. This study aims to analyze Indonesian military law concerning unauthorized marriages, focusing on Military Criminal Case Number 143 K/MIL/2016 involving a TNI AL soldier. The research examines unauthorized marriages within the military context. It employs a descriptive-analytical approach by analyzing Indonesian military law regarding marriage permissions and a concrete case of unauthorized marriage by a TNI AL soldier. The results indicate that in this case, the defendant, who married without permission, was charged with violating Article 279, Paragraph (1) of the Indonesian Criminal Code. Although a 7-month imprisonment sentence was imposed, this decision raises questions about the appropriateness and effectiveness of the sanctions in preventing unauthorized marriages. The study's implications highlight the need for broader regulations governing marriage permissions in the military to more effectively address this issue. The research concludes that unauthorized marriages remain a significant issue that needs to be addressed seriously within the military environment.